199 Improving training in systems leadership management: a 'Mini-Darzi' approach. Issue 6 (27th May 2022) - Wu, Kit; Tahir, Mehreen; Adams, Sarah; Ellis, Cathy; Larcombe, Karen; King, Rachel; Dilley, Michael; Malby, Rebecca
Abstract : Introduction: Leadership and management development is mandated by General Medical Council as core skills for all doctors [GMC, 2012]. Yet, the myriad of leadership courses for trainees are delivered by external organisations without opportunities for concrete applications in the NHS setting. Aims: To develop a short applied leadership and management course appropriate for doctors in training using peer-learning approach, and to review its impact through objective feedback from participants' implementation of projects. Method and Results : A management and leadership course was developed using a peer-learning approach by three Darzi fellows participating in leadership development programme and project-based attachments to NHS organisations [Malby, 2018]. The course follows a three-stage approach: a one-day workshop to impart knowledge and skills in systems change; a quality improvement project in the par- ticipants' workplace; finishing with a workshop for participants to showcase their project and feedback. Results and Summary: The course educates participants in clinical leadership in the NHS and equip them with the tools to manage new challenges. The application of knowledge in the participants' workplace through implementation of a systems change project allows for greater understanding of quality improve- ment within NHS healthcare. In turn, it will encourage participants to seek further opportunities to develop their skills and lead change projects in their future careers. kitwu@doctors.org.uk